1. The yz-plane is the plane x = 0.
So, The general rule of reflection over the yz- plane is (x,y,z) →(−x,y,z)
===========================================
2. Applying the rule found in (1)
the new points of the shape after this reflection will be
P(–1, 2, 0) ⇒⇒⇒ P'(1, 2, 0)
Y(2, 3, 0) ⇒⇒⇒ Y'(-2, 3, 0)
R(–3, 4, 0) ⇒⇒⇒ R'(3, 4, 0)
A(–2, 1, 5) ⇒⇒⇒ A'(2, 1, 5)
=============================================
3. Applying the transformation rule (x, y, z) → (x + 2, y + 4, z – 3)
to the points from number 2
P'(1, 2, 0) ⇒⇒⇒ P" (3 , 6 , -3 )
Y'(-2, 3, 0) ⇒⇒⇒ Y" (0 , 7 , -3)
R'(3, 4, 0) ⇒⇒⇒ R" ( 5 , 8 , -3)
A'(2, 1, 5) ⇒⇒⇒ A" ( 4 , 5 , 2)